Information Exposure as the Dominanat Variable Associated with Stunting in Adolescents - Nur Annisa Julianti; Nino Adib Chifdillah; Dian Ardyanti (Formosa Journal of Science and Technology, 2023)
The 2018 Riskesdas report states that East Kalimantan ranks 23rd as the province with the highest prevalence of stunting in Indonesia, especially in Kutai Kartanegara Regency. The purpose of this study was to analyze the determinants of knowledge about stunting in students of SMK Muhammadiyah Loa Kulu. This study used a cross sectional design with proportional random sampling and simple random sampling techniques. The population of this study was 140 and the sample was 104 people. Data collection was done by filling out a questionnaire. The results showed a relationship between gender (ρ=0.002), information exposure (ρ=0.000), and health worker support (ρ=0.000) with respondents' knowledge about stunting. The results of multivariate analysis showed that the dominant variable associated was information exposure (PR 5.04). Based on the results of the study, the most dominant variable associated with the knowledge of SMK Muhammadiyah Loa Kulu students is information exposure.